Variation in the μ-Opioid Receptor Gene (OPRM1) Does Not Moderate Social-Rejection Sensitivity in Humans. (July 2019) - Persson, Emil; Asutay, Erkin; Heilig, Markus; Löfberg, Andreas; Pedersen, Nancy; Västfjäll, Daniel; Tinghög, Gustav
Given previous findings from animal studies and small-scale studies in humans, variation in the μ-opioid receptor gene ( OPRM1 ) has been proposed as a strong biological candidate for moderating sensitivity to social rejection. Using a substantially larger sample ( N = 490) than previous studies, a prospective genotyping strategy, and preregistered analysis plans, we tested the hypotheses that OPRM1 variation measured by the functional A118G polymorphism (rs1799971) moderates (a) dispositional sensitivity to rejection and feelings of distress following social exclusion and (b) decision making involving social cognition. In three experimental tasks commonly used to assess altruism, reciprocity, and trust in humans, we found no evidence in favor of the hypotheses; nine main tests were preregistered, and all of them yielded small and statistically insignificant estimates. In secondary analyses, we used Bayesian inference and estimation to quantify support for our findings. Taken together, our results strongly suggest that the link between OPRM1 A118G variation and social-rejection sensitivity is weaker than previously thought.